Biogenic Silver Nanoparticles as a Post-surgical Treatment for Corynebacterium pseudotuberculosis Infection in Small Ruminants - Santos, Laerte Marlon; Stanisic, Danijela; Menezes, Ulisses José; Mendonça, Marcos Antônio; Barral, Thiago Doria; Seyffert, Núbia; Azevedo, Vasco; Durán, Nelson; Meyer, Roberto; Tasic, Ljubica; Portela, Ricardo Wagner (Frontiers in Microbiology, 2019)
Caseous lymphadenitis (CL) is an infectious and zoonotic disease characterized by the development of granulomas in the lymph nodes and internal organs of small ruminants. The etiological agent of this disease is Corynebacterium pseudotuberculosis, a Gram-positive and facultative intracellular bacterium. The conventional treatment for CL consists of drainage and chemical cauterization of the lesions using a 10% iodine solution. However, this type of treatment is not effective, due to iodine’s cytotoxic profile and low antibacterial activity. Currently, silver nanoparticles (AgNPs) can be seen as an alternative treatment for CL due to their antimicrobial activity and wound healing effects. Therefore, the present study aimed to evaluate AgNPs as a post-surgical treatment for CL. Twenty-nine goats and sheep with clinical signs of CL were selected. Surgical intervention was performed to excise the caseous lesions. To treat the lesions, an ointment formulation based on AgNP mixed with natural waxes and oils was used in the experimental group, and the conventional treatment with 10% iodine was used in the control group. Bacteria were isolated from the excised caseous material. The animals were observed for 8 weeks after the surgical treatment, and blood samples were taken weekly. The surgical wounds of sheep treated with AgNP healed faster, and the surgical wound area was smaller during the observation period; the latter effect was also observed in goats. AgNP-treated animals also had less purulent discharge and less moisture in the surgical wounds. The AgNP-treated animals had lower leukocyte counts and lower titers of anti-C. pseudotuberculosis antibodies. There was no statistically significant difference between the groups with regard to the hemogram results. The results of the susceptibility testing of C. pseudotuberculosis strains (T1, 1002, FRC41, and VD57 strains) and clinical isolates to AgNPs showed growth inhibition, even at low concentrations. It can be concluded that post-surgical treatment of CL using the AgNP-based ointment may be a promising tool in the control of CL, through faster healing, decreased wound contamination, and no apparent toxic effects.